Enhanced photovoltage for inverted planar heterojunction perovskite solar cells - Luo, D; Yang, W; Wang, Z; Sadhanala, A; Hu, Q; Su, R; Shivanna, R; Trindade, GF; Watts, JF; Xu, Z; Liu, T; Chen, K; et al. (American Association for the Advancement of Science, 2018)
The highest power conversion efficiencies (PCEs) reported for perovskite solar cells (PSCs) with inverted planar structures are still inferior to those of PSCs with regular structures, mainly because of lower open-circuit voltages (Voc). Here we report a strategy to reduce nonradiative recombination for the inverted devices, based on a simple solution-processed secondary growth technique. This approach produces a wider bandgap top layer and a more n-type perovskite film, which mitigates nonradiative recombination, leading to an increase in Voc by up to 100 millivolts. We achieved a high Voc of 1.21 volts without sacrificing photocurrent, corresponding to a voltage deficit of 0.41 volts at a bandgap of 1.62 electron volts. This improvement led to a stabilized power output approaching 21% at the maximum power point.